2018
DOI: 10.1186/s12874-018-0642-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the International Physical Activity Questionnaire (IPAQ) for assessing moderate-to-vigorous physical activity and sedentary behaviour of older adults in the United Kingdom

Abstract: BackgroundIn order to accurately measure and monitor levels of moderate-to-vigorous physical activity (MVPA) and sedentary behaviour (SB) in older adults, cost efficient and valid instruments are required. To date, the International Physical Activity Questionnaire (IPAQ) has not been validated with older adults (aged 60 years plus) in the United Kingdom. The current study aimed to test the validity of the IPAQ in a group of older adults for both MVPA and SB.MethodsParticipants wore an Actigraph GT3X+ for seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
201
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(221 citation statements)
references
References 49 publications
10
201
0
10
Order By: Relevance
“…Additional studies examined and compared the criterion validity of self-report measures under the following conditions: nine studies (19 comparisons) on weekday/ workday (includes time at work and outside of work) vs. weekend/non-workday sedentary time [24,47,51,58,69,70,86,156,198]; 2 studies (5 comparisons) on minutes per day of self-reported television time [141,155]; nine studies (11 comparisons) on minutes per day of occupational sedentary time [61,65,75,99,101,105,122,136,181,188,193]; and, four studies (five comparisons) on the proportion of a workday spent sedentary [91,105,158,205]. In all of these studies a comparable criterion was required (e.g., self-reported occupational sitting was compared to accelerometer sedentary time during work time only).…”
Section: Validitymentioning
confidence: 99%
“…Additional studies examined and compared the criterion validity of self-report measures under the following conditions: nine studies (19 comparisons) on weekday/ workday (includes time at work and outside of work) vs. weekend/non-workday sedentary time [24,47,51,58,69,70,86,156,198]; 2 studies (5 comparisons) on minutes per day of self-reported television time [141,155]; nine studies (11 comparisons) on minutes per day of occupational sedentary time [61,65,75,99,101,105,122,136,181,188,193]; and, four studies (five comparisons) on the proportion of a workday spent sedentary [91,105,158,205]. In all of these studies a comparable criterion was required (e.g., self-reported occupational sitting was compared to accelerometer sedentary time during work time only).…”
Section: Validitymentioning
confidence: 99%
“…Remembering sedentary time across multiple sedentary behaviors appears to be quite difficult after just 1 day, and Study 1 demonstrated that some participants were unsure up to ±5 hours over the past‐week. In previous studies, the inaccuracy of other weekly sedentary questionnaires has been demonstrated using the Bland‐Altman analysis showing very wide limits of agreement . The results of these previous studies in combination with the results of Study 2 suggest that the most accurate measures of weekly sedentary time may come from a questionnaire that has participants report daily sedentary time across multiple sedentary behaviors sequentially, in more of a “log” format, rather than retrospectively, such as the NIGHTLY‐WEEK‐U.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that continuous reporting of past‐day sedentary time over a week could make a participant aware of how much sitting they are participating in, and as a result, begin to limit their daily sedentary time. The downside of this limitation will need to be weighed against the demonstrated inaccuracies of past‐week or typical week sedentary time questionnaires . A further limitation of the NIGHTLY‐WEEK‐U is the increased burden displaced on both the participant and the researcher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations